2016
DOI: 10.1111/gcb.13475
|View full text |Cite
|
Sign up to set email alerts
|

Coarse climate change projections for species living in a fine‐scaled world

Abstract: Accurately predicting biological impacts of climate change is necessary to guide policy. However, the resolution of climate data could be affecting the accuracy of climate change impact assessments. Here, we review the spatial and temporal resolution of climate data used in impact assessments and demonstrate that these resolutions are often too coarse relative to biologically relevant scales. We then develop a framework that partitions climate into three important components: trend, variance, and autocorrelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 68 publications
0
60
0
Order By: Relevance
“…Lastly, surveys spaced over four decades might miss potentially important temporal variability both in climate and morph frequency changes. The temporal and spatial variability in climate and an increasing frequency of extreme events (Buckley et al 2012, Vasseur et al 2014) might explain some site-specific responses better than simple hypotheses equating morph frequencies to mean climate variables (Gibbs and Karraker 2006, Moore and Ouellet 2015, Nadeau et al 2017. This result has been demonstrated in repeated surveys of polymorphic land snail species, which show correlations between morph frequency changes and climate variation across multiple time periods (Cameron andPokryszko 2008, Johnson 2011).…”
Section: Modelmentioning
confidence: 96%
“…Lastly, surveys spaced over four decades might miss potentially important temporal variability both in climate and morph frequency changes. The temporal and spatial variability in climate and an increasing frequency of extreme events (Buckley et al 2012, Vasseur et al 2014) might explain some site-specific responses better than simple hypotheses equating morph frequencies to mean climate variables (Gibbs and Karraker 2006, Moore and Ouellet 2015, Nadeau et al 2017. This result has been demonstrated in repeated surveys of polymorphic land snail species, which show correlations between morph frequency changes and climate variation across multiple time periods (Cameron andPokryszko 2008, Johnson 2011).…”
Section: Modelmentioning
confidence: 96%
“…SDMs the appropriate spatial resolution depends on the species considered, as large and mobile organisms might be well-represented by large-scale climatic conditions, whereas small and less mobile species might not (Nadeau, Urban, & Bridle, 2017). This also strongly depends on the data source considered, as range maps at a high resolution typically result in incorrect spatial patterns of species richness (Hurlbert & Jetz, 2007).…”
Section: Current Patterns Of Species Richnessmentioning
confidence: 99%
“…In primary forests and secondary forests re‐growing on abandoned farmland, previous studies found that organisms—particularly ectotherms—avoid suboptimal temperatures in the wider “macroclimate” (climate at a spatial scale of m to ha) by moving locally into “microclimates”: climate at a fine‐scale, mm to m, that is distinct from the macroclimate (González del Pliego et al., ; Scheffers, Brett, Diesmos, Williams, & Evans, ; Scheffers, Evans, Williams, & Edwards, ). Climate at this fine‐scale is more relevant for the majority of terrestrial biodiversity, which primarily consists of small‐bodied ectotherms (Nadeau, Urban, & Bridle, ; Potter, Arthur Woods, & Pincebourde, ; Suggitt et al., ). Indeed, the vast proportion of terrestrial species are small in size, flat in shape, or thermoregulate via contact with a substrate, and so it is important to consider microclimates close to, and including, the surfaces on which these species live (Kaspari, Clay, Lucas, Yanoviak, & Kay, ; Scheffers et al., ).…”
Section: Introductionmentioning
confidence: 99%